2009
DOI: 10.1111/j.1558-5646.2009.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Discordant Distribution of Populations and Genetic Variation in a Sea Star With High Dispersal Potential

Abstract: Patiria miniata, a broadcast-spawning sea star species with high dispersal potential, has a geographic range in the intertidal zone of the northeast Pacific Ocean from Alaska to California that is characterized by a large range gap in Washington andOregon. We analyzed spatial genetic variation across the P. miniata range using multilocus sequence data (mtDNA, nuclear introns) and multilocus genotype data (microsatellites). We found a strong phylogeographic break at Queen Charlotte Sound in British Columbia tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
108
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 58 publications
(119 citation statements)
references
References 100 publications
(128 reference statements)
9
108
0
2
Order By: Relevance
“…C. pentagona has relatively modest levels of genetic diversity when compared with other asterinid sea stars with planktonic development [32,50]; however, C. hystera shows a dramatic reduction in nucleotide diversity, allelic diversity and most notably heterozygosity (see electronic supplementary material, table S1). Only one microsatellite locus is polymorphic across the entire known range of this species, and this locus is completely fixed within populations.…”
Section: Results (A) Molecular Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…C. pentagona has relatively modest levels of genetic diversity when compared with other asterinid sea stars with planktonic development [32,50]; however, C. hystera shows a dramatic reduction in nucleotide diversity, allelic diversity and most notably heterozygosity (see electronic supplementary material, table S1). Only one microsatellite locus is polymorphic across the entire known range of this species, and this locus is completely fixed within populations.…”
Section: Results (A) Molecular Diversitymentioning
confidence: 99%
“…DNA extraction, PCR amplification, sequencing and genotyping all followed the protocols in Keever et al [32,33]. All individuals were genotyped at five microsatellite loci (including three shared between species): a108, b202, b227, b231 and c219 were used in C. pentagona; loci a102, b202, b227, c219 and d8 were used for C. hystera.…”
Section: Methodsmentioning
confidence: 99%
“…In these situations, the only evolutionary force acting on allele frequencies in these populations will be genetic drift, which has larger effects on smaller effective population sizes 38 , and has been shown to be rampant in artificially fragmented populations 39 . Therefore, considering the high genetic diversity of P. miniata and previous connectivity 17 , we would expect to see a more pronounced signal of anthropogenic isolation in the mtDNA markers, which have an effective population ~1/4 the size of the nDNA markers 38 . In all population structure models tested, we observed that R 2 values were ~1.5-30 times higher for mtDNA markers relative to nDNA markers (Tables 2-4), although results from nDNA genetic diversity regressions were consistent with anthropogenic isolation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…17 with the exception of using dye-labelled primers and an ABI 3730XL for genotyping. Two mtDNA loci were sequenced, a tRNA region and part of the cytochrome oxidase subunit I gene (COI) 17 and control region (CR) 42 . The two mtDNA loci were analysed as a LD marker (COI) and as a full mtDNA marker (COI + CR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation